Growing with the wind. - Katz, M.J.; Acevedo, J.M.; Wappner, P. (Fly, 2014)
In this Extra View we comment on our recent work on Sudestada1 (Sud1), a Drosophila 2-oxoglutarate (2OG)-dependent dioxygenase that belongs to the Ribosomal Oxygenase (ROX) subfamily. Sud1 is required for normal growth in Drosophila, and is conserved in yeast and mammals. We reported that Sud1 hydroxylates the ribosomal protein S23 (RPS23), and that its loss of function restricts growth and provokes activation of the unfolded protein response, apoptosis and autophagy. In this Extra View we speculate on the role that RPS23 hydroxylation might play in stop codon recognition and on the possible link between Sud1 loss-of-function and activation of the Unfolded Protein Response, Stress Granules formation and growth impairment.